2017
DOI: 10.1159/000455270
|View full text |Cite
|
Sign up to set email alerts
|

Role of Autophagy in Angiogenesis Induced by a High-Glucose Condition in RF/6A Cells

Abstract: Purpose: To study the effect of autophagy on vitality, migration, and tube formation of RF/6A cells under the condition of D-glucose. Methods: Cultured RF/6A cells were randomly divided into 4 groups (control, low glucose, high glucose, and high glucose with 3-methyladenine [3-MA]). Autophagy-related proteins (Atg7, p62, and LC3) were monitored. Cell vitality, cell migration, tube formation, reactive oxygen species (ROS) production, and apoptosis were assessed. Results: Cell vitality significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Besides, autophagy level in the hypoxia+ 3-MA group was still higher than that of the control group because autophagy maintained at a basic level for the controls. As 3-MA was reported to function only when activation of cell autophagy occurs, the 3-MA alone group was not set for detecting autophagy activation and cell migration and tube formation in RVECs under hypoxia [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, autophagy level in the hypoxia+ 3-MA group was still higher than that of the control group because autophagy maintained at a basic level for the controls. As 3-MA was reported to function only when activation of cell autophagy occurs, the 3-MA alone group was not set for detecting autophagy activation and cell migration and tube formation in RVECs under hypoxia [ 28 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…From fever onset, the elevation rate of the total APN levels was 1.46-fold more than that of HMW APN. Oligomerisation is a significant determinant of flux across endothelial monolayers, as LMW APN is preferentially transported, and the rapid increase in absolute quantity of total APN in the plasma seems more effective at controlling fulminant inflammation [16, 17, 42]. From the febrile/hypotensive stage to the diuretic/convalescent stage, the elevation rate of the HMW APN levels was 1.63-fold more than that of total APN.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the role of APN in promoting revascularisation and immunomodulation, we hypothesised that APN is involved in the pathogenesis of HFRS. Du et al have studied changes in the total APN level in the plasma of patients with HFRS and found that total APN was elevated and associated with disease severity [16]. Interestingly, HMW APN has the highest binding activity, which is considered the most physiologically active form [9, 17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, chloroquine as a pharmacological autophagy inhibitor could synergize the sunitinib anti-cancer effect by limiting angiogenic capacity probably through upregulation of inducible nitric oxide synthase, increased reactive nitrogen species production, and an increase of anti-oxidant capacity [ 166 ]. Moreover, starvation-induced autophagy in cultured BAECs triggered the cell migration and in vitro angiogenesis by activating of VEGF and AKT protein while the use of Atg-5 siRNA reversed the autophagy pro-angiogenic effects on BAECs [ 167 ]. It is noteworthy that retinal ECs have a contradictory behavior in comparison with ECs of peripheral vessels.…”
Section: The Correlation Between Autophagy and Angiogenesismentioning
confidence: 99%
“…It is noteworthy that retinal ECs have a contradictory behavior in comparison with ECs of peripheral vessels. In RF/6A cell line, autophagy as a positive regulator contributed to the hypoxia or high glucose-induced neovascularization under different stress conditions [ 167 , 168 ] (Fig. 3 ).…”
Section: The Correlation Between Autophagy and Angiogenesismentioning
confidence: 99%